Recent Advances in Reliability and Quality in Design - Pham, Hoang (Springer, 2017)
Recent Advances in Reliability and Quality in Design presents the latest theories and methods of reliability and quality, with emphasis on reliability and quality in design and modeling. Each chapter is written by active researchers and professionals with international reputations, providing material which bridges the gap between theory and practice to trigger new practices and research challenges.